Unverricht-Lundborg disease: development of splicing therapeutic approaches for a patient with an homozygous mutation in the cystatin B gene - Matos, Liliana (2013)
Unverricht-Lundborg disease (ULD or EPM1) is the most common form of progressive myoclonic epilepsy (PME) worldwide. It is an autosomal recessive neurodegenerative disorder caused by mutations in the cystatin B gene (CSTB) that encodes an inhibitor of several lysosomal cathepsins. An unstable expansion, missense, nonsense, frameshift and mutations that may lead to alternative splicing have been described as causal of EPM1. Recently, our group described an ULD patient who is homozygous for a new synonymous mutation (c.66G>A; p.Q22Q) located at the last nucleotide of exon 1. The transcriptional profile analysis allowed the identification of two CSTB splice variants, one of normal size with the G>A change and other with partial inclusion of intron 1 due to activation of a cryptic splice-site inside the intronic sequence. To correct the splice defect, here we developed antisense oligonucleotide and U1snRNA mediated therapeutic strategies. U1 is required for splice donor site (SDS) recognition of pre-mRNAs and initiates the splicing process. The mutation c.66G>A interferes with the recognition of the SDS by U1. In a first approach, to reduce missplicing from CSTB gene, we generated four U1 construct isoforms with increasing complementarity to the SDS. Transfection of patient-derived fibroblasts with different concentrations of the adapted U1 vectors did not allowed the correction of the aberrant transcript. In a second strategy, we have designed a specific lock nucleic-acid (LNA) oligonucleotide to block the activated cryptic splice-site in intron 1. Normal splicing pattern of a single transcript with the synonymous change G>A was successfully rescued after LNA transfection in patient cells. The therapeutic effect showed to be dose-dependent. These results suggest that antisense therapy might be a potential alternative or adjunct treatment strategy for patients holding splicing changes in CSTB gene. As far as we know this is the first report of a patient tailored therapy in cells of an ULD patient.